Pengaruh Kualitas E-Service terhadap Minat Beli Konsumen (Studi Kasus pada Website Koren Denim) - Rendi Maulana; Kezia Kurniawati (Jurnal Manajemen Maranatha, 2014)
Internet users in Indonesia are increasing, creating an opportunity for business people to do business through e-commerce on the company website. Each company would have the marketing strategy to attract consumers, one of them by providing electronic services facility or called e-service on the website. Through the role of e-service on e-commerce, companies can improve service quality through reliability aspect (X1), website design (X2), security/privacy (X3) and customerservice (X4) to attract consumers buying interest (Y) so that the quality of online services can improve consumer buying interest through the company's website. This research was aimed to analyze the influence of e-service quality to consumersbuying interest on Koren Denim’s website, through purposive sampling of 150 respondents and analyzed by using multiple regression analysis. The result showed that the e-service quality had positive influence on consumers buying interest at 38%with a significance value of 0.000 (<0.05), indicating that H1 was accepted and generated the regression equation Y = 5.035 + 0.440 X1 + 0.296 X2 + 0.187 X3 + 1.820 X4.Keywords: e-commerce, e-service, quality of service and buying interest